2005
DOI: 10.1111/j.0022-202x.2005.23806.x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation Normalizes Mutagenesis of Mitochondrial DNA as Well as Functional Consequences

Abstract: Mutations of mitochondrial (mt) DNA play a role in neurodegeneration, normal aging, premature aging of the skin (photoaging), and tumors. We and others could demonstrate that mtDNA mutations can be induced in skin cells in vitro and in normal human skin in vivo by repetitive, sublethal ultraviolet (UV)-A-irradiation. These mutations are mediated by singlet oxygen and persist in human skin as long-term biomarkers of UV exposure. Although mtDNA exclusively encodes for the respiratory chain, involvement of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 41 publications
4
81
1
3
Order By: Relevance
“…Sharov et al 26 showed that exogenous phosphocreatine administration attenuated ischemic damage and reduced necrotic zone with maintenance of membrane integrity. Berneburg et al 27 reported that there was a link between mitochondrial DNA mutations and cellular energy metabolism. In addition, authors showed that mitochondrial mutagenesis could be normalized by creatine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Sharov et al 26 showed that exogenous phosphocreatine administration attenuated ischemic damage and reduced necrotic zone with maintenance of membrane integrity. Berneburg et al 27 reported that there was a link between mitochondrial DNA mutations and cellular energy metabolism. In addition, authors showed that mitochondrial mutagenesis could be normalized by creatine supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…HFs were homogenized, and genomic DNA was isolated by the Wizard SV genomic DNA purification system (Promega, Mannheim, Germany) following the manufacturer's instructions. Detection of the common deletion was performed as described previously 38,61 and levels of the common deletion and undeleted mitochondrial DNA sequences were detected with real-time PCR. The normalized level of common deletion in vehicle-treated follicles (ϭ1) was compared with the normalized common deletion level of 4-HC-treated follicles.…”
Section: Detection Of Mitochondrial Common Dna Deletionmentioning
confidence: 99%
“…23 In addition, antiinflammatory activities of creatine on endothelial cells have been shown recently. 4 Berneburg et al 5 observed that creatine supplementation normalized ultraviolet-A-irradiation induced mitochondrial mutagenesis and showed the link between mtDNA common deletion rate and energy Notes: Values are expressed as mean ± Standard deviation * median (minimum-maximum). When groups were evaluated in terms of progress, no significant difference was found in all three groups (p ¼ 0.959, 0.594, and 0.173, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Creatine has been reported to have antiinflammatory, antioxidant effects and it has been shown that it acts as a free radical scavenger. [4][5][6][7][8] Besides this, recent reports supported that Cr has additional beneficial effects on various neurological, muscular, cardiovascular disorders, and aging. [9][10][11][12][13][14] The aim of this study is to investigate the possible protective effect of creatine therapy on cisplatin-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 88%